Multislice computerized tomography coronary angiography can be a comparable tool to intravascular ultrasound in evaluating “true” coronary artery bifurcations - Radunović, Anja; Vidaković, Radosav; Timčić, Stefan; Odanović, Natalija; Stefanović, Milica; Lipovac, Mirko; Krupniković, Kosta; Mandić, Aleksandar; Kojić, Dejan; Tomović, Milosav; Ilić, Ivan (Frontiers in Cardiovascular Medicine, 2023)
Aim Coronary bifurcation atherosclerosis depends on its angles, flow, and extensive branching. We investigate the ability of CT coronary angiography (CTCA) to determine atherosclerotic plaque characteristics of “true” bifurcation compared with intravascular ultrasound (IVUS) and the influence on side branch (SB) fate after percutaneous coronary intervention (PCI). Methods and results The study included 70 patients with 72 “true” bifurcations. Most of the bifurcations were in the left anterior descending—diagonal (Dg) territory [50 out of 72 (69.4%)]. Longitudinal plaque evaluation at the polygon of confluence [carina and 5 mm proximal and distal in the main branch (MB)] showed that carina side MB and SB plaque had occurred with the lowest incidence with fibro-lipid structure (115 ± 63 HU and 89 ± 73 HU, p < 0.001 for all). Bland–Altman analysis showed a discrepancy in measuring mainly the lumen area between CTCA and IVUS in proximal MB [lumen 5.10, 95% CI (95% confidence interval, 4.53–5.68) mm2, p < 0.001; vessel −1.42, 95% CI (−2.63 to −0.21) mm2, p = 0.023], carina MB [lumen 3.74, 95% CI (3.37–4.10) mm2, p < 0.001; vessel −0.48, 95% CI (−1.45 to 0.48) mm2, p = 0.322], and distal MB [lumen 4.72, 95% CI (4.27–5.18) mm2, p < 0.001; vessel 0.62, 95% CI (−0.53 to 1.77) mm2, p = 0.283]. A significant correlation existed between average plaque density on CTCA with a percentage of calcified plaque on IVUS tissue characterization (proximal r = 0.307/p = 0.024, carina 0.469/0.008, distal 0.339/0.024, minimal lumen diameter 0.318/0.020). Circumferential plaque in the proximal MB segment remained an independent predictor of SB compromise [OR 3.962 (95% CI 1.170–13.418)]. Conclusion Detection and characterization of atherosclerotic plaque by CTCA in non-left main “true” coronary bifurcations can provide useful information about bifurcation anatomy and plaque distribution that can predict outcomes after provisional stenting, thus guiding the interventional strategy to bifurcation PCI.